Meningkatkan Bakat Anak melalui Keseruan Perlombaan Gebyar Muharram Kel. Tanah Seribu, Kec. Binjai Selatan - Nurhayati Nurhayati; Yasmina Fajri; Evi Sukma Pratiwi; Raisah Armayanti Nasution; Hilda Zahra Lubis (BADAN PENERBIT STIEPARI PRESS, 2025)
The Community Service Program (PEMA) in Tanah Seribu District by the State Islamic University of North Sumatra (UINSU) aims to develop children's talents and enthusiasm for learning through various competitions during the Gebyar Muharram celebration. This activity includes coloring, adhan, short verse recitation, and ranking competitions, which were participated in by 65 children. Through this program, children are taught to develop skills, increase self-confidence, and foster a sense of unity and mutual cooperation among the community. The results show an increase in the children's skills and enthusiasm, as well as active community participation in supporting the success of this program. The method used in this study was a qualitative method, which uses field observation and describes programs or activities. Natural research methods conducted directly in the field rather than in a laboratory are called qualitative research. This type of approach focuses on natural phenomena or symptoms. Therefore, another name for this research might be field study or naturalistic investigation.